Stress in students of nursing: na a integrative review - Susan Bublitz; Laura de Azevedo Guido; Etiane de Oliveira Freitas; Luis Felipe Dias Lopes (Revista de Enfermagem da Universidade Federal de Santa Maria, 2012)
Objective: to analyze the scientific production regarding stress in nursing students. Method: this integrative review has been conducted in the databases BDENF and LILACS and the electronic library SCIELO, with the association of the descriptor Nursing student with the keyword stress. For a description of selected research used the absolute (n), percentage (%) and categorization of data by similarity. Results: 16 studies have been selected in which 37.5% are related to stressors in the academic life of Nursing students, 37.5% regarding coping strategies in university life, and 25% in relation to signs and symptoms of stress. Stressors are present in the course of undergraduate nursing and reflect the quality of life, since scholars have signs and symptoms resulting from stress. Conclusion: suggested that the undergraduate courses to develop proposals to minimize stress in order to make the academic environment of nursing more productive and less stressful